Identification of Hypermobile Scars on Tympanic Membrane Using Automatic Tympanometry - J, Dayalan Samuel; VU, Nandur; D’Mello, Joan (Journal of All India Institute of Speech and Hearing)
Three subjects exhibited abnormal, atypical tympanographs when tested with electromedics 86 AR Tympanometer. These tympanographs were similar to Ad type, but with a clear notch. Repeated measures yielded similar findings. Ipsilateral reflexes were present in all these ears. Microscopic examination revealed fine, thin, hypermobile scars. Patients with flaccid tympanic membrane yielded d type tympanographs without a notch. The notched tympanographs obtained in tympanometer 86 AR seem to help in differential diagnosis.